English teachers’ knowledge of using ICT in English language teaching in Nepal - Khadka, Bishnu Kumar; Shahi, Dhruba Kumar (American Journal of STEM Education, 2025)
In this study, we investigate English teachers’ knowledge and application of Information and Communication Technology (ICT) in English Language Teaching (ELT) in Nepal. A quantitative survey of 222 secondary-level English teachers in western Nepal revealed moderate ICT proficiency across hardware usage, educational software, and internet surfing. English Teachers exhibited higher competency in basic computer operations, such as using keyboards, word processors, and email communication. Still, they struggled with tasks like preparing interactive whiteboard materials, using plagiarism detection tools and integrating ICT into traditional teaching. The findings highlight the necessity of professional development programs to improve digital literacy and practical ICT skills. Additionally, policy interventions are essential to address infrastructural challenges and foster an enabling environment for ICT integration in ELT.